Effective practices for meeting the learning needs of ‘superdiverse’ multi-language learners in early childhood classrooms - Csillik Éva („RIK-U” Kft., 2018)
Abstract. The challenges of multilingual/multicultural education in our contemporary world are numerous as previously highlighted by Csillik (2018, in press); therefore, there is an indispensable need for further inquiries and future research studies to propose in order to improve the quality of education in ‘superdiverse’ classrooms. Since this field is still unexplored and in the need for immediate improvement the author aims to widen one’s repertoire of effective teaching practices in order to provide the best education possible for multilingual/multicultural learners in ‘superdiverse’ early childhood classrooms of today and the upcoming future.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: multilingual/multicultural education; anti-bias education; effective practices; superdiversity; translanguaging